High‐dose steroid therapy for acute respiratory distress syndrome lacking common risk factors: predictors of outcome. Issue 2 (25th October 2017) - Kinoshita, Yoshiaki; Ishii, Hiroshi; Kushima, Hisako; Watanabe, Kentaro; Fujita, Masaki
Abstract : Aim: Acute respiratory distress syndrome (ARDS) is a life‐threatening lung disease that usually occurs in patients with the underling risk factors that triggers lung inflammation. We sometimes encounter patients with ARDS lacking common risk factors. Recent studies have indicated the effectiveness of corticosteroids for this cohort. However, the characteristics of survivors with ARDS who lack common risk factors, and who received high‐dose methylprednisolone pulse therapy (MPPT), are not known. Methods: We undertook a retrospective study of patients with ARDS lacking common risk factors, who received i.v. MPPT for 3 days. The patients ( n  = 46) were classified into two groups, survivors ( n  = 23) and non‐survivors ( n  = 23), based on their survival at 60 days after the initiation of MPPT, and their clinical and radiological parameters were evaluated. Results: The patient characteristics and disease severity of the two groups were comparable. The percentage of consolidation/(ground‐glass attenuation [GGA] + consolidation) on the chest computed tomography scans of survivors was significantly lower than that of non‐survivors (survivors, 5.63% [2.31–13.8] versus non‐survivors, 27.2% [5.97–41.4]; P  =   0.01). In the stratified analysis, the percentage of consolidation/(GGA + consolidation) was significantly associated with 60‐day survival. Conclusions: Our results show that the percentage of consolidation/(GGA + consolidation) on the chest CT scans is an independent prognostic factor for patients with ARDS lacking common risk factors after MPPT. Abstract : Acute respiratory distress syndrome (ARDS) is usually resistant to treatment, but ARDS lacking common risk factors sometimes shows responsiveness to corticosteroid treatment. We found that the low percentage of consolidation/(ground‐glass attenuation + consolidation) on chest computed tomography scans was associated with a significant increase in 60‐day survival in patients with ARDS lacking common risk factors.